Development of anti-Helicobacter pylori immunoglobulins Y (IgYs) in quail - Najdi, S. (Iran J Vet Res, 2016)
Helicobacter pylori (H. pylori) is a gram-negative, microaerophilic bacterium that cause the stomach infection in more than 50% of human population worldwide. The aim of this study was to examine the possibility of anti-H. pylori immunoglobulins Y (IgYs) production in quails and evaluate the effect of the different methods of immunization on titers of IgY in egg yolks. Whole cell bacterial antigen was used for immunization of quails. Forty Japanese quails (Coturnix japonica) were divided into four groups. The first group intramuscularly immunized with one dose of antigen (3 × 10(8) inactivated bacteria) whereas the second group injected with half dose. Third group administered orally. Yolk IgY was isolated using precipitation method of water dilution combined with chloroform. Dot-blot and ELISA (enzyme-linked immunosorbent assay) were used for determining the specificity and quantifying the titer of IgY in egg yolks. Results showed that quails as well as chickens are able to produce anti-H. pylori IgY. Quails antibodies have high titer and specificity that can be used in therapeutic and research purposes. This study indicated that higher amounts of antigen can not develop higher titer of IgY and injection is not necessary for efficient immunization of the quail against H. pylori.